Nanoparticle-Based Rice Husk Liquid Smoke as Periodontitis Therapy through OPG, RANK, and RANKL Expression - Ira Arundina; Theresia Indah Budhy; Aqsa Sjuhada Oki; Meircurius Dwi Condro Surboyo; Arvind Babu Rajendra Santosh; null Sidarningsih; Indeswati Diyatri; Tytania Rahmaputry; Arya Pradana; Mohammad Iqbal; Azzahra Salsabila Adira Moelyanto (International Journal of Biomaterials)
Introduction. Periodontitis therapy employing nanomaterials with submicron sizes holds promise for enhancing osteogenesis and facilitating periodontal cell proliferation. This study aims to assess the potential of nanoparticle-based rice husk liquid smoke (n-RHLS) in an animal model of periodontitis by evaluating the expression of osteoprotegerin (OPG), receptor activator of nuclear factor-kβ (RANK), and receptor activator of nuclear factor-kβ ligand (RANKL). Methods. Twenty-eight male Wistar rats were inoculated with 109 CFU/ml of Porphyromonas gingivalis in the sulcus mandibular incisor region to create periodontitis and subsequently treated with n-RHLS while the control with saline. Immunohistochemical staining was performed on the mandibular incisor to assess OPG, RANK, and RANKL expression 2 and 7 days after treatment. Results. OPG expression exhibited a significant increase at both 2 and 7 days, while RANKL expression decreased notably after 7 days of treatment using n-RHLS (p<0.05). In contrast, RANK expression did not show significant differences compared to the control groups (p>0.05). Conclusion. Nanostructured liquid smoke derived from rice husk nanoparticles (n-RHLS) demonstrates potential as a therapeutic agent for periodontitis, especially on OPG/RANK/RANKL expression, by modulating OPG and RANKL expression to support periodontal tissue health.